Las respuestas literarias a álbumes ilustrados en contextos multiculturales - Colomer, Teresa; Margallo, Ana María (Linguarum Arena, 2018)
The research presented addresses the need to integrate into the educational system the immigrant children and explores the role of the discussion of literary texts in the language and cultural reception of newcomers. Studies of language learning in multilingual contexts (Guasch, 2010; Siqués Jofre, 2008; Vila, Siquéand Roig, 2006) highlight educational practices focused toshared meaning construction, knowledge of the school language and attention to the processes of identity construction in the success of the process. The research carried out by the GRETEL team at the Universitat Autonoma de Barcelona is in this line and addresses specifically the incidence of interpretive discussion of picture books in multilingual classrooms. The first part of the article summarizes the methodology of experimentation on the activities for the shared construction of meaning. The second part analyses some of the responses given by the children during the process of interpretation of the books, in particular, the answers focusing the compositional aspects and intertextual aspects of the texts. These results provide information both on the possibilities of literary activities in the process of reception of immigrant students, as well as on the way in which children construct the meaning of texts in situations of collective discussion.